Dental Health Physical Exercise (SKG) for Elderly - Khotimah, Fridaniyanti Khusnul; Sosiawan, Agung; Santosa, Lintang Maudina; Sudiartha, Nancy Cynthia; Pande, I Ketut Brahma; Romadhona, Widya Rizky; Pangestika, Elvira Widya; Rachmaningayu, Ulyasari; Saputra, Benny; Amarilda, Faila Shofa; Priyanridania, Erika; Bramantoro, Taufan (Indonesian Journal of Dental Medicine, 2019)
Background: Late adulthood is an aging process characterized by a decrease in some bodily functions. Physical changes associated with late adulthood are musculoskeletal disorders, changes in the cardiovascular system, changes in the immune system, and changes in physical activity. Physical exercise is one of the ways to improve elderly' physical activities. An epidemiological study on elderly under Jagir Public Health Center coverage area reported that periodontitis and dental caries could lower physical performance in the elderly, lowering physical activity. Purpose: In consideration of theproblem in question, a promotive and preventive program is needed. The Dental Health Physical Exercise (SKG) program was expected to improve the overall physical condition of the elderly. Methods: The "Senam Kesehatan Gigi dan Mulut” took place on 19 July 2019 at Integrated Health Service Post for Elderly. Results: There were 26 elderly participated in physical exercise. 7.7% of them were not able to follow the exercise, and the remaining 92.3% were able to follow the exercise. Conclusion: 92.3% of 26 elderly were able to follow the exercise properly and correctly. However, the remaining 7.7% of them were not able to catch up with the physical exercise. In addition, most participants were able to perform 4 out of 5 movements criteria.